The extended mid-infrared structure of the circinus galaxy - Packham, C; Radomski, J; Roche, P; Aitken, D; Perlman, E; Alonso-Herrero, A; Colina, L; Telesco, C (Institute of Physics Publishing, 2005)
We present subarcsecond resolution mid-IR images of the Circinus galaxy at 8.74 and 18.33 μm. We resolve extended emission at both wavelengths, extending ∼2″ from each side of the nucleus in an approximate east-west direction. These extensions are spatially coincident with previously detected compact (∼30 pc) V-shaped [O III] emission extending northwest of the nucleus as well as countercone [Si vi] emission, emission at these wavelengths interpreted as delineating the interface between inflowing material and the ionization cone. We detect no extended mid-IR emission associated with the structure responsible for collimating the ionizing photons (i.e., obscuring torus or disk of material), limiting the flux density of the obscuring structure to ≤0.27 mJy or a diameter of ≤0″.20 (≤4 pc).